MANAJEMEN KARIR TANPA BATAS - Muniya Alteza (Program Studi Manajemen, 2017)
The dynamic, turbulent and constantly changing business environment dictates the rise of new organizational structure which is more flexible and adaptive, called boundaryless organization. This phenomena must followed by the shift of human resource practise included career management. The traditional career paradigm which considered employee as an individual who entered the a firm, worked hard, performed well, was loyal and commited and thus received greater rewards and job security has been replaced by a new paradigm based on continous learning and identity change. The new boundaryless career contract, protean career are characterized by psychological success as the ultimate career individual must be able to acquire metaskills, that is learning how to learn. An effective career management conducted by both individual and organization also needed to manage a successful boundaryless career for employee.